PENGARUH ZAKAT PRODUKTIF DAN JENIS ZAKAT SERTA JUMLAH PENDISTRIBUSIAN TERHADAP PENDAPATAN MUSTAHIK PADA LEMBAGA AMIL ZAKAT PUPUK KALTIM BONTANG (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2019)
Nur Rofiq, 2019. The Infuence Zakat Productive and Kinds of Zakat with Quantity of Distributing Toward Mustahik Income at LAZ PKT Bontang city. Supervising Lecturer: Prof. Dr. H. Zamruddin Hasid, S.E., S.U, Supervisor I and Dr. Juliansyah Roy, S.E., M.Si, Supervisor II.This Research purpose to know influence zakat productive and kind of zakat with quantity of distributing toward mustahik income at LAZ PKT Bontang city.The research has carried out at Bontang City, Borneo. This research is a kind quantitativ research and use formula is analysis double regression with dummy variabel. The collecting data is with library method, quizioner method and documents method. The quantity population on this research is fourty five respondents becomes foundings of LPEM LAZ PKT Bontang city. The result on this research is zakat productive and kind of zakat with quantity of distributing positive influential toward mustahik income.